Associations between match-play characteristics and environmental temperatures in 4 professional football leagues - Schwarz, E.; Duffield, R.; Novak, A. R.; Compton, D. A.; Meyer, T. (European Journal of Sport Science, 2025)
This study investigated the association between environmental temperature and match-play characteristics (shooting, passing, dribbling and defending) in four professional football leagues. Twenty-seven performance indicators (PI's) were collated from 1585 matches from the German Bundesliga 1 and 2, Spanish La Liga and Australian A-League. Environmental data were obtained for dry-bulb temperature (T) and wet-bulb globe temperature (WBGT) retrospectively from public sources. For each league, linear regressions were used to determine relationships between PI's and T and WBGT and linear mixed models were used to determine those associations across all four leagues. Individual leagues showed varying associations between a collection of PI's and environmental measures. When combining the four leagues' match data, 8 of the 17 investigated parameters were associated with T and WBGT (p < 0.002). Passes, especially short passes, were reduced in higher T (-2.3 [-3.1 to -1.5] and p < 0.001) and WBGT (-3.1 [-4.0 to -2.1] and p < 0.001), alongside an increase in the success rate of passes (0.06 [0.02-0.09] and p = 0.001). The number of passes into the opponent's final third was reduced for both T (-0.18 [-0.25 to -0.05] and p = 0.001) and WBGT (-0.17 [-0.28 to-0.05] and p = 0.002), but the number of key passes leading to a shot or goal was not associated with T or WBGT (p = 0.67). The number of touches, take-ons and turnovers were reduced in higher T and WBGT (all p < 0.001). Accordingly, in higher heat stress, match actions, especially those performed at high volumes, are reduced. Therefore, teams should expect a possibly altered match play and may consider adapting tactical or heat-mitigating strategies to counter these effects.